Exame vestibular: um estudo sobre a voz da escola na imprensa - Santos, Maria do Rosário de Fátima de Aguiar Sá Barreto dos (2008)
As from an analyze of a hundred writings made by the applicants to the Language and Literature course of the Universidade Federal de Minas Gerais (UFMG) in the exams of 1983, Costa Val noticed that 73% of the texts presented problems related to informativity, mainly due to unexpectedness and data sufficiency. Taking this study as a first step, our paper.s proposal, is to identify the factors that contribute to this issue. Considering the contribution of authors that approached the media issue and the social image construction around the language and the language teaching, we focused the relationship between the language teaching, the writing teaching and the press in a structure composed by 33 (thirty three) news about the exams to enter into an University, published in the days that precede and follow this event, mainly the news about the Pernambuco.s Public Universities writing exams. The source of this news was the two biggest newspapers in our state: o Jornal do Comércio and the Diário de Pernambuco. These texts were analyzed under the light of the methodological-theory reference of the Speech Critical Analysis. With this analysis we concluded that the press, when announcing the School speech, contributes to perpetuate the language teaching practice and consequently, the Writing, factors of the unsatisfying functioning of the applicants. texts informativity